2020
DOI: 10.3389/fpsyg.2020.01464
|View full text |Cite
|
Sign up to set email alerts
|

How Numerical Unbalance Constraints Physical and Tactical Individual Demands of Ball Possession Small-Sided Soccer Games

Abstract: This study aimed to explore the effects of playing different unbalanced ball possession small-sided games on external workload (distance covered while walking, running, and sprinting, and max speed), tactical individual actions (number of passes with dominant and non-dominant foot), and internal load (rating of perceived exertion, RPE) in under-23 soccer players. Participants played 4v2, 4v3, 4v4, 4v5, and 4v6 small-sided games (SSGs) on a 30 × 25 m playing area. Data were analyzed under an opponent-based pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
1
10
1
Order By: Relevance
“…By contrast, in shorter defensive play phases, the change of the role from offensive to defensive may induce aggressive behaviour related to ball recovery, and thus greater external loads. This behaviour may be strengthened by the numerical superiority of the offensive team, meaning that the defensive team may be working as a unit and waiting for the right moment to apply pressure (Nunes et al, 2020). With regard to internal load responses, previous investigations have shown contradictory results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, in shorter defensive play phases, the change of the role from offensive to defensive may induce aggressive behaviour related to ball recovery, and thus greater external loads. This behaviour may be strengthened by the numerical superiority of the offensive team, meaning that the defensive team may be working as a unit and waiting for the right moment to apply pressure (Nunes et al, 2020). With regard to internal load responses, previous investigations have shown contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed no differences in TRIMPmod and HRmax between SSGs when the defensive phase was 30 s, 1 min or 2 min. Probably, the minority transition between phases of play with specific periods of defence induced specific pacing strategies in the teams (Nunes et al, 2020), provoking a decrease in exercise intensity during this phase. Although our results did not show Articles published in the Journal of Human Kinetics are licensed under an open access Creative Commons CC BY 4.0 license.…”
Section: Discussionmentioning
confidence: 99%
“…Other previous constraints and tactical behaviors more closely related to this constraint such as player’s unbalanced or the limitation in the ball touches can increase the external physical load through the players’ distributions, the increase in the speed of the ball or the type of defender marking derived from the tasks and limitations. These constraints showed increases both in internal and external load [ 15 , 26 ]. However, the level of the participants (semi-professionals) or the complexity of the task designed could be the key to the results of the present study, due to a greater number of errors in the pass and less effective time of practice [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, we hypothesize (1) that the restrictions in pass decisions will increase the internal and external physical load of the soccer tasks. To justify this hypothesis, we highlight that previous studies that used constraints like the limitation of ball touches or unbalance have observed an increase in one vs. one duels, the distance covered, and Rated Perceived Exertion Scale (RPE) values [ 15 , 26 , 27 ]. Additionally, in our opinion, to achieve the objectives during pass limitations tasks, players must optimize the space and increase the speed of the ball, which can increase the physical demands [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that playing with one less defender (i.e., 5v4) does not impact the team’s defensive ability to interrupt passes or shots, and playing with two less defenders (i.e., 5v3) generates significant changes in the offenses’ behavior, driving them to create more opportunities for shooting, scoring, and passing [ 12 ]. As originally intended, evidence from recent studies in soccer confirmed quantitatively that unbalanced situations induce distinct physical, technical, and tactical behaviors based on numerical inequality [ 13 ]. Indeed, in basketball, modifying SSGs in order to train the practice objective can change the environment characteristic.…”
Section: Introductionmentioning
confidence: 91%